PENGARUH SIKAP KEUANGAN LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN MELALUI PERILAKU KEUANGAN SEBAGAI VARIABEL INTERVENING DI 25 PUSKESMAS SERTA 1 LABKESDA KABUPATEN BONDOWOSO - Lestiyono, Dwi Budi; Arief, Mohammad Yahya; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze the influence of variablesFinancial Attitudes Financial Literacy and Financial Inclusion towards Financial Management Through Financial Behavior as an Intervening Variable in 25 Community Health Centers and 1 Labkesda, Bondowoso Regency. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application. Financial attitudes have a significant positive effect on financial behavior (H1 is accepted), Financial literacy has a significant positive effect on financial behavior (H2 is accepted), Financial inclusion has a positive but not significant effect on financial behavior (H3 is rejected), Financial attitudes have a significant positive effect on financial management (H4 is accepted), Financial literacy has a significant positive effect on financial management (H5 is accepted), Financial inclusion has a positive but not significant effect on financial management (H6 is rejected), Financial behavior has a significant positive effect on financial management (H7 is accepted), Financial attitude has a positive but significant effect not significant on financial management through financial behavior (H8 is rejected), financial literacy has a positive but not significant effect on financial management through financial behavior (H9 is rejected), and financial inclusion has a positive but not significant effect on financial management through financial behavior (H10 is rejected).